2009
DOI: 10.3748/wjg.15.4156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early preoperative 5-fluorouracil on the integrity of colonic anastomoses in rats

Abstract: AIM:To determine the effect of chemotherapy on wound healing by giving early preoperative 5-fluorouracil (5-FU) to rats with colonic anastomoses. METHODS:Sixty Albino-Wistar male rats (median weight, 235 g) were used in this study. The rats were fed with standard laboratory food and given tap water ad libitum . The animals were divided into three groups:Group 1: Control group (chemotherapy was not administered), Group 2: Intraperitoneally (IP) administered 5-FU group (chemotherapy was administered IP to animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
2
10
0
1
Order By: Relevance
“…The majority of studies on anastomosis healing have used hydroxyproline content at the anastomosis site as a measure because it (with proline and glycine) is a component of collagen [10]. In the present study, the level of hydroxyproline was greater in group M than in group C at 7 days postoperatively.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The majority of studies on anastomosis healing have used hydroxyproline content at the anastomosis site as a measure because it (with proline and glycine) is a component of collagen [10]. In the present study, the level of hydroxyproline was greater in group M than in group C at 7 days postoperatively.…”
Section: Discussionsupporting
confidence: 58%
“…Injections were repeated until the 6th postoperative day (a total of 7). In previous studies, the number of injections ranged from 2 to 7 after surgery [5,6,7,8,10,17]. We chose the maximum number of injection to allow for an adequate contrast in collagen regeneration rates between groups C and M. Because of this, we accepted a higher mortality rate for group M.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Ozel et al, Kanellos et al, Morris in their experimental study, concluded that intravenous 5-FU delayed, but did not prevent healing, and that it would be safe to use it in the postoperative period, but not until several days after operation. [25][26][27] In this study seizures was noted in 1 case. This might be due to hypocalcemia and hypomagnesemia in patients that receive intensive chemotherapy, especially cisplatin, with over-hydration.…”
Section: Discussionmentioning
confidence: 84%
“…Various outcomes have been reported in the studies investigating the effects of 5-FU on wound healing. 31,[37][38][39][40][41][42] Nonetheless, 5-FU is the cytotoxic agent of choice in colorectal cancer CT and has the characteristics of existing on the peritoneal surface for long term and passing into the portal circulation in high amounts. 42 In the present study we used 5-FU together with preoperative RT.…”
Section: Discussionmentioning
confidence: 99%